Biodegradable Plasticized Blends of Poly(L-lactide) and Cellulose Acetate Butyrate: From Blend Preparation to Biodegradability in Real Composting Conditions - Kunthadong,P. (Springer New York, 2015)
© 2014, Springer Science+Business Media New York. Biodegradable blends of poly(L-lactide) (PLL) and cellulose acetate butyrate (CAB) were prepared as 40–60 µm thick films cast from solution using chloroform as a solvent. Both poly(ethylene glycol) (PEG) and a polyester adipate (Paraplex G40) were used as plasticizers to decrease the PLL/CAB blends’ glass transition temperature and make them more flexible. Ternary PLL/CAB/PEG blends showed only partial compatibility due to phase separation of crystalline PLL-rich and CAB-rich domains. In contrast, when Paraplex G40 was used as the plasticizer, it produced PLL/CAB/Paraplex G40 blends with stable morphology over an extended period of time with much reduced phase separation. The PLL/CAB/plasticizer blend films all degraded in real composting conditions at PLL contents of over 50 wt%. Moreover, the PEG-plasticized ternary blend films showed complete degradability at PLL ≥ 70 and CAB ≤ 30 wt%. These results suggest that the CAB content and plasticizer type can be used to tune polymer blend compatibility and biodegradability. The most promising formulations were found to be PLL/CAB/Paraplex G40 blends with compositions of PLL ≥ 70, CAB ≤ 30 and Paraplex G40 = 20 parts by weight, combining good polymer compatibility and biodegradability with a suitable balance of mechanical properties.